Association Between Living With Parents And Not Living With Parents With Psychological Stress In Preclinical Medical Students In University Of Pelita Harapan - Engelberta Pardamean; Andrew Theodorous Timothy (Fakultas Kedokteran Universitas Pelita Harapan, 2020)
Introduction: Stress is a response to stressor that came from the body (internal or external). According to several studies, medical student very evident to experience of stress, which compared to student from other major. In previous studies the level of stress among medical student was 45% – 72%. And lack data that connect stress with domisil in medical student, and one of the reasons for this research. Objective To find an association between domisil and psychological stress in medical students. Material and Methods This research is categorical comparative analytic, with cross sectional as the design study and needed 264 repondent that consis of preclinic medical student of Pelita Harapan University. Taken by questionnaire from GHQ – 12 for the data. Data will be analyzed using Chi – Square in SPSS version 23.Results: This result showed 43 (41%) students who experiencing psychologic stress and 62 students (59%) students who not experiencing psychologic stress in students who live with their parents. There’s also 104 (65.4%) students who experiencing psychologic stress and 55 (34.6%) students who not experiencing psychologic stress in students who don’t live with their parents. This research has a significant result with p-value <0.001 that support the hypothesis.Conclusions: There is an associaton between domisil and psychological stress in preclinic medical student at Pelita Harapan